Głosowanie elektroniczne – nowe wyzwanie dla demokracji? - Musiał-Karg, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The notion of democracy poses a significant challenge and problem in modern considerations on history, philosophy and politics. At present, in the face of the so-called information revolution, democracy has undoubtedly undergone profound and easily visible transformations. It can be said that the application of IT to exercise democratic power has brought about a revolution that will span a period of many years, given the different potential differing states have to spread the new technologies. The development of information and communications technology (ICT) has introduced new notions related to democracy, such as teledemocracy, technopolitics or electronic democracy (e-democracy). The subject of this paper, electronic voting (e-voting) is among the highly significant instruments of e-democracy. Electronic voting is the fulfillment of the principle of national sovereignty as it can be applied in the procedures of both indirect (e-elections) and direct (e-referendum) democracy.
Keywords: E-voting; Demokracja